Impact of Colonoscopy Bowel Preparation Quality on Follow-up Interval Recommendations for Average-risk Patients With Normal Screening Colonoscopies: Data From the New Hampshire Colonoscopy Registry. Issue 4 (April 2020) - Butterly, Lynn F.; Nadel, Marion R.; Anderson, Joseph C.; Robinson, Christina M.; Weiss, Julia E.; Lieberman, David; Shapiro, Jean A.
Abstract : Background and Aims: National guidelines for colonoscopy screening and surveillance assume adequate bowel preparation. We used New Hampshire Colonoscopy Registry (NHCR) data to investigate the influence of bowel preparation quality on endoscopist recommendations for follow-up intervals in average-risk patients following normal screening colonoscopies. Methods: The analysis included 9170 normal screening colonoscopies performed on average risk individuals aged 50 and above between February 2005 and September 2013. The NHCR Procedure Form instructs endoscopists to score based on the worst prepped segment after clearing all colon segments, using the following categories: excellent (essentially 100% visualization), good (very unlikely to impair visualization), fair (possibly impairing visualization), and poor (definitely impairing visualization). We categorized examinations into 3 preparation groups: optimal (excellent/good) (n=8453), fair (n=598), and poor (n=119). Recommendations other than 10 years for examinations with optimal preparation, and >1 year for examinations with poor preparation, were considered nonadherent. Results: Of all examinations, 6.2% overall received nonadherent recommendations, including 5% of examinations with optimal preparation and 89.9% of examinations with poor preparation. Of normal examinations with fair preparation, 20.7% of recommendations were for an interval <10 years. Among those examinations with fair preparation, shorter-interval recommendations were associated with female sex, former/nonsmokers, and endoscopists with adenoma detection rate ≥20%. Conclusions: In 8453 colonoscopies with optimal preparations, most recommendations (95%) were guideline-adherent. No guideline recommendation currently exists for fair preparation, but in this investigation into community practice, the majority of the fair preparation group received 10-year follow-up recommendations. A strikingly high proportion of examinations with poor preparation received a follow-up recommendation greater than the 1-year guideline recommendation. Provider education is needed to ensure that patients with poor bowel preparation are followed appropriately to reduce the risk of missing important lesions.